On the wind turbine blade loads from an aeroelastic simulation and their transfer to a three-dimensional finite element model of the blade. Issue 6 (December 2020) - Forcier, Louis-Charles; Joncas, Simon
This article first presents a description of the different load types to which a wind turbine blade is subjected. Analytical equations are derived to express blade loads from operation parameters of the wind turbine (rotor and nacelle velocities and accelerations; pitch, coning, tilt, and azimuth angles; blade mass properties; turbine geometry). This allows a better understanding of the contribution of each of these parameters to the total load on a blade. A difficulty arises for transferring the loads computed by an aeroelastic model (a one-dimensional model of the blade) to a three-dimensional finite element model of the blade. A method is proposed for that purpose. It consists in applying the aerodynamic loads using RBE3 elements and applying gravitational and inertial loads as volume forces. Finally, an example of this method used for the design of a 10 kW wind turbine blade is presented.